2008
DOI: 10.1007/s11274-008-9774-7
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble granules containing Bacillus megaterium for biological control of rice sheath blight: formulation, bacterial viability and efficacy testing

Abstract: Endospores of B. megaterium were formulated in granule formulations with sodium alginate, lactose and polyvinylpyrrolidone (PVP K-30) by the wet granulation technique. The granule formulation exhibited good physical characteristics, such as high-water solubility and optimal viscosity, that would be suitable for spray application. The bacteria remained viable in the dry granule formulation at 10 9 c.f.u./g after 24 months storage at room temperature. Under laboratory conditions, aqueous solutions of the formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…A suspension of B. megaterium endospores was prepared as described by Chumthong et al (2008). The bacterium was cultured in potato dextrose broth (PDB) at 30-35 °C, stirring at 200 rpm for 4 days, and bacterial cells at the stationary growth stage were separated by centrifugation at 3,000 rpm for 10 min.…”
Section: Preparation Of Bacterial Endospore Suspensionmentioning
confidence: 99%
“…A suspension of B. megaterium endospores was prepared as described by Chumthong et al (2008). The bacterium was cultured in potato dextrose broth (PDB) at 30-35 °C, stirring at 200 rpm for 4 days, and bacterial cells at the stationary growth stage were separated by centrifugation at 3,000 rpm for 10 min.…”
Section: Preparation Of Bacterial Endospore Suspensionmentioning
confidence: 99%
“…Vegetative cells are more susceptible to environmental stress compare to endospores. However, Chumthong et al (2008) observed that application of an equivalent number of un-formulated endospores resulted in much loss of the bacterial endospores even 1 day after application. Furthermore chili bead producing by method described seemed not to uniform.…”
Section: Discussionmentioning
confidence: 94%
“…In Thailand, research on the use of biological control to suppress plant pathogens has been carried out with damping-off of cucumber Diseases of crops & vegetables (Intana 2003), leaf blight of bambara groundnut (Pengnoo et al 2006) and sheath blight of rice (Wiwattanapatapee et al 2004;Wiwattanapatapee et al 2007;Chumthong et al 2008). Some of these studies have led to the commercialisation of the biological control agent, Trichoderma harzianum (Intana 2003) for control of soil-borne plant pathogens.…”
Section: Introductionmentioning
confidence: 99%